TEACHER FRIENDLY E-FLASHCARD: A DEVELOPMENT OF BILINGUAL LEARNING MEDIA FOR YOUNG LEARNERS - Tirtayani, Luh Ayu; Magta, Mutiara; Lestari, Ni Gusti Ayu Made Yeni (Universitas Pendidikan Ganesha, 2017)
The study aims to describe the development of process design and validation of learning media 'friendly teacher e-flashcards' through empirical test on a limited group. 'Teacher friendly e-flashcards' is the media that was developed to meet the needs of bilingual learning at the level of early childhood education. The development of educational media is implemented in four stages: a preliminary study, development, evaluation, and reflection as well as documentation. At this stage of development, the content is prepared first and then proceed with the design of the program. Validation of the content and media experts shows that the 'teacher friendly e-flashcards' is being 'very good' for stimulation bilingual early childhood. Furthermore, empirical tests on a limited group (12 kindergarten teachers from four districts in Bali) gave judgment on the category of 'good'. Media 'teacher friendly e-flashcards' is a technology-based educational media that can be used in bilingual teaching of children of kindergarten in Bali. Further media development and empirical testing in a wider group strongly recommended for subsequent research